The Linkage of Skills and Sophistication of Alutsista / Weapons Makes Pride and Increases State Revenue in the Defense Industry through the Field of Resilience Sports - Jefri Bachtiar; I.B Putra Jandhana; Timbul Siahaan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Defense Industry is a central element in maintaining national security, requiring the alignment of military personnel with the sophistication of the main weapons system (alutsista). This article examines the crucial dynamics that tie individual skills in the military to the effective use of advanced defense equipment. The focus is on the evolution of military technology and the need to develop personnel skills in response to these advances. The Defense Industry is the backbone of national security, which requires synergy between the skills of military personnel and the sophistication of the main weapons system (alutsista). This article discusses the crucial link between individual skills in the military and the successful use of advanced defense equipment. Furthermore, the article explains the latest military technological innovations that influence the development of progress and the need for appropriate personnel skill development. By integrating sports skills as a promotional instrument, the article discusses the role of international military tournaments as a vehicle for strengthening the defense industry's image. Active involvement in agility sports not only creates national pride but also stimulates positive coverage in the media, providing a significant boost to the promotion of the defense industry. A wise marketing approach is needed to exploit the appeal of agility sports to educate and captivate the global market. Targeted marketing strategies can utilize agility sports as a tool to promote the defense industry, create emotional ties with the community, and, no less important, increase state revenues through increasing exports of defense equipment. This article also covers effective marketing approaches to maximize the benefits of agility sports involvement in increasing the appeal of the defense industry globally. By detailing case studies of countries that have successfully implemented this strategy, this article concludes that the integration of skills, advanced defense equipment, and promotion of agility sports is a holistic approach that has the potential to advance the defense industry, create national pride, and generate significant revenue increases for the country.